Reassessing Capital Structure and Profitability: Evidence from Indonesia’s Distribution Sector - Dwianika, Agustine (Journal of Financial and Behavioural Accounting, 2025)
This study investigates the relationship between capital structure and financial performance in distribution companies listed on the Indonesia Stock Exchange, employing a quantitative explanatory approach. Capital structure is assessed using leverage indicators based on debt-to-equity and debt-to-asset measures, while financial performance is evaluated through return on equity. The findings reveal that capital structure does not exert a significant influence on profitability, either individually or collectively. This suggests that financing composition is not a primary determinant of financial outcomes in the distribution sector. As such, firms are encouraged to focus more on operational efficiency, asset management, and marketing strategies to enhance profitability. The study offers theoretical and practical insights for both management and investors, and highlights the need for further research into alternative factors affecting financial performance.